Spatial conservation planning with ecological and economic feedback effects - Larrosa, C; Carrasco, LR; Tambosi, LR; Banks-Leite, C; Milner-Gulland, EJ (Elsevier, 2019)
Most spatial conservation prioritisations being implemented across the globe are based on static approaches to conservation planning. These use snapshots of systems to support decision-making. However, ignoring the dynamic nature of systems can result in misleading spatial prioritisations and missed opportunities to encourage participation in conservation programmes. Using a modelling approach, we show that integrating economic and ecological feedbacks into conservation planning improved social and ecological outcomes. We developed an approach that enabled accounting for feedbacks of farmland set-asides using a popular conservation planning tool. We empirically assessed the impact of ignoring feedbacks on plans to restore the Brazilian Atlantic Forest by comparing outcomes of our approach and a widely used static approach. The proposed approach attained better conservation outcomes than a static approach, at about 7% lower cost, while also allowing more farmers to benefit economically from the set-aside scheme through capitalising on the differences between their opportunity costs and the amount paid by the scheme. Accounting for feedbacks led to substantially different areas being prioritised for farmland set-asides, and to more farmers being included in the set-aside scheme. These results show important benefits from understanding, and then working with, feedbacks that inevitably accompany large-scale conservation interventions. Our approach is the first to integrate both environmental and economic feedbacks into spatial conservation planning, and model information rent capture. In doing so, it demonstrates how existing economic incentives can be used to encourage farmers to join a conservation set-aside, while still resulting in a lower overall intervention cost.